Identificaciónde Bacilos Gram Negativos productores de Carbapenemasas en heces de Felis catus - Díaz Sánchez, Isis Gabriela (Machala : Universidad Técnica de Machala, 2025)
Carbapenemases (CP)are β-lactamase enzymes with high hydrolytic capacity, capable of degrading penicillins, cephalosporins, monobactams, and carbapenems, significantly reducing the efficacy of β-lactam antibiotics. This study evaluated the prevalence of carbapenemase-producing Gram-negative bacilli (CPGNB) in domestic cats from Ecuador, a topic scarcely explored in the region.Rectal swabs were collected from 120 cats treated at three veterinary clinics in Machala between October 2023 and March 2024. Samples were processed using CHROMagar™KPC chromogenic medium, and bacteria were identified through biochemical tests and the Enterosystem 18R system. Additionally, a structured survey was conducted to assess risk factors associated with CPGNB colonization.The results revealed a 7.5% prevalence of CPGNB, identifying strains of Escherichia coli, Klebsiella spp., Citrobacter spp., Acinetobacter spp., and Pseudomonas spp.. Nine strains exhibited resistance to imipenem and meropenem. Statistical analysis indicated that self-medication and coprophagy were significant risk factors associated with CPGNB colonization (p< 0.05). In contrast, other factors such as prolonged antibiotic treatment, hospitalization, and raw meat consumption did not show significant associations (p> 0.05).Given that carbapenems are "last-resort antibiotics," their efficacy is at risk due to the horizontal transfer of resistance genes through plasmids and transposons. This study highlights the need to implement surveillance systems to monitor antimicrobial resistance in companion animals and to conduct further research on the factors promoting colonization by carbapenemase-producing bacteria in domestic cats
Las carbapenemasas (CP) son enzimas β-lactamasas con alta capacidad hidrolítica, capaces de degradar penicilinas, cefalosporinas, monobactámicos y carbapenémicos, reduciendo significativamente la eficacia de los antibióticos β-lactámicos. Este estudio evaluó la prevalencia de bacilos Gram negativos productores de carbapenemasas (CPBGN) en gatos domésticos de Ecuador, un tema escasamente explorado en la región.Se analizaron hisopados rectales de 120 gatos atendidos en tres clínicas veterinarias de Machala entre los meses de octubre del 2023 a marzo del 2024. Las muestras fueron procesadas utilizando medio cromogénico CHROMagar™KPC y las bacterias identificadas mediante pruebas bioquímicas y el sistema Enterosystem 18R. Además, se aplicó una encuesta estructurada para evaluar factores de riesgo asociados a la colonización por CPBGN.Los resultados revelaron una prevalencia del 7,5% de CPBGN, identificándose cepas de Escherichia coli, Klebsiella spp., Citrobacter spp., Acinetobacter spp. y Pseudomonas spp. Nueve cepas mostraron resistencia a imipenem y meropenem. Los análisis estadísticos indicaron que la automedicación y la coprofagia fueron factores de riesgo significativamente asociados con la colonización por CPBGN (p < 0,05). En contraste, otros factores como el tratamiento prolongado con antibióticos, hospitalización y consumo de carne cruda no mostraron asociaciones significativas (p > 0,05).Dado que los carbapenémicos son "antibióticos de último recurso", su eficacia está en riesgo debido a la transferencia horizontal de genes de resistencia mediante plásmidos y transposones. Este estudio resalta la necesidad de implementar sistemas de vigilancia para monitorear la resistencia antimicrobiana en animales de compañía, así como de realizar investigaciones adicionales sobre los factores que promueven la colonización por bacterias productoras de carbapenemasas en gatos domésticos
Keywords: CARBAPENEMICOS; CARBAPENEMASAS; RESISTENCIA BACTERIANA; FACTORES DE RIESGO